Evaluation a systematic approach - Rossi, Peter H. (Peter Henry) 1921-2006.; Freeman, Howard E. (Newbury Park, Calif. Sage Publications, 1989)
This textbook in its fourth edition is substantially reorganized with examples and references updated. New are: richer treatment of formative evaluation procedures; deeper examination of cost effectiveness; a more practical approach to costs benefits analysis; full exploration of the issues regarding the utilization of evaluations; updated coverage of qualitative research and examples from the late 80's; a realistic view of practical ethics.
Preface -- 1. Programs, policies, and evaluations -- 2. Diagnostic procedures -- 3. Tailoring evaluations -- 4. Program monitoring for evaluation -- 5. Strategies for impact assessment -- 6. Randomized designs for impact assessment -- 7. Non-randomized designs for impact assessment -- 8. Measuring efficiency -- 9. The social context of evaluation -- References -- Author index -- Subject index -- About the authors.
Includes bibliographical references (p. 469-487).
Keywords: Evaluation research (Social action programs)